Introducing the Practice Dive Approach: an extension of co-creation in physical activity promotion and health promotion. (11th December 2021) - Popp, Johanna; Carl, Johannes; Grüne, Eva; Pfeifer, Klaus
Summary: Recently, there has been increasing interest in co-creation utilized for physical activity (PA) promotion and health promotion. Co-creation involves researchers and non-academic stakeholders conjointly developing and implementing interventions. In addition to the frequently reported benefits of co-creation, critical voices highlight the associated challenges (e.g. different interests that inhibit interaction). So far, research has not identified concrete solutions to these challenges and the limitations of co-creation. This article aims to introduce the Practice Dive Approach as a potential way to strengthen cooperation between researchers and non-academic stakeholders. We build on real-life experiences from a German research project, in which researchers moved into practice to familiarize themselves with the settings and end-users. After conducting a literature search on related concepts in PA/health promotion, we developed a comprehensive approach to fostering multi-sectoral cooperation. The introduced Practice Dive Approach assumes that a significant contribution to better cooperation among co-creators is the temporal immersion of researchers in their setting of interest, which has the potential to improve the success of co-creation in the PA/health promotion field. A four-level typology characterizes the intensity of researcher interactions with the setting and the non-academic stakeholders. Potential beneficial effects for both researchers and non-academic stakeholders can be hypothesized (e.g. familiarity with the setting structures and increased understanding of the end-users), while simultaneously, some challenges need to be considered. Future research should aim to validate the concept and its postulated effects. Lay Summary: Collaboration among researchers and non-academic stakeholders is increasingly used to promote physical activity and health. For example, people involved in such collaborations jointly develop new interventions. Potential challenges include different interests or work routines that can complicate cooperation. This article aims to introduce the Practice Dive Approach as a potential way to improve cooperation between researchers and non-academic stakeholders. We developed the approach based on observations from a German research project and a literature search on related concepts. This approach assumes that the temporal involvement of researchers in their setting of interest can strengthen research-practice cooperation and improve its success. We describe different types of a Practice Dive and the requirements for conducting Practice Dive activities. Furthermore, we present the potential effects of a Practice Dive for the researchers and the non-academic stakeholders, such as increased familiarity between both groups. However, some challenges need to be considered when applying the Practice Dive Approach. Future research should test this approach and its potential effects.